Inhaled nitric oxide in the management of persistent pulmonary hypertension of the newborn: a meta-analysis - Oliveira, Carlos Augusto Cardim de; Troster, Eduardo J; Pereira, Crésio R (Revista do Hospital das Clínicas, 2000)
OBJECTIVES: To evaluate the use of inhaled nitric oxide (NO) in the management of persistent pulmonary hypertension of the newborn. METHODS: Computerized bibliographic search on MEDLINE, CURRENT CONTENTS and LILACS covering the period from January 1990 to March 1998; review of references of all papers found on the subject. Only randomized clinical trials evaluating nitric oxide and conventional treatment were included. OUTCOMES STUDIED: death, requirement for extracorporeal membrane oxygenation (ECMO), systemic oxygenation, complications at the central nervous system and development of chronic pulmonary disease. The methodologic quality of the studies was evaluated by a quality score system, on a scale of 13 points. RESULTS: For infants without congenital diaphragmatic hernia, inhaled NO did not change mortality (typical odds ratio: 1.04; 95% CI: 0.6 to 1.8); the need for ECMO was reduced (relative risk: 0.73; 95% CI: 0.60 to 0.90), and the oxygenation was improved (PaO2 by a mean of 53.3 mm Hg; 95% CI: 44.8 to 61.4; oxygenation index by a mean of -12.2; 95% CI: -14.1 to -9.9). For infants with congenital diaphragmatic hernia, mortality, requirement for ECMO, and oxygenation were not changed. For all infants, central nervous system complications and incidence of chronic pulmonary disease did not change. CONCLUSIONS: Inhaled NO improves oxygenation and reduces requirement for ECMO only in newborns with persistent pulmonary hypertension who do not have diaphragmatic hernia. The risk of complications of the central nervous system and chronic pulmonary disease were not affected by inhaled NO.